Organellar phylogenomics of Ophioglossaceae fern genera - Kuo, Li-Yaung; Su, Huei-Jiun; Koubínová, Darina; Xie, Pei-Jun; Whitehouse, Christopher; Ebihara, Atsushi; Grant, Jason R. (Frontiers in Plant Science, 2024)
Previous phylogenies showed conflicting relationships among the subfamilies and genera within the fern family Ophioglossaceae. However, their classification remains unsettled where contrasting classifications recognize four to 15 genera. Since these treatments are mostly based on phylogenetic evidence using limited, plastid-only loci, a phylogenomic understanding is actually necessary to provide conclusive insight into the systematics of the genera. In this study, we have therefore compiled datasets with the broadest sampling of Ophioglossaceae genera to date, including all fifteen currently recognized genera, especially for the first time the South African endemic genus Rhizoglossum. Notably, our comprehensive phylogenomic matrix is based on both plastome and mitogenome genes. Inferred from the coding sequences of 83 plastid and 37 mitochondrial genes, a strongly supported topology for these subfamilies is presented, and is established by analyses using different partitioning approaches and substitution models. At the generic level, most relationships are well resolved except for few within the subfamily Ophioglossoideae. With this new phylogenomic scheme, key morphological and genomic changes were further identified along this backbone. In addition, we confirmed numerous horizontally transferred (HGT) genes in the genera Botrypus, Helminthostachys, Mankyua, Sahashia, and Sceptridium. These HGT genes are most likely located in mitogenomes and are predominately donated from angiosperm Santalales or non-Ophioglossaceae ferns. By our in-depth searches of the organellar genomes, we also provided phylogenetic overviews for the plastid and mitochondrial MORFFO genes found in these Ophioglossaceae ferns.